2021
DOI: 10.1002/aqc.3736
|View full text |Cite
|
Sign up to set email alerts
|

Social, spatial and isotopic niche partitioning identify an estuarine community of bottlenose dolphins as a discrete management unit

Abstract: 1. Investigations of population structure across multiple niche dimensions can identify discrete management units within populations. This study examined social, spatial and isotopic niche partitioning in Indo-Pacific bottlenose dolphins (Tursiops aduncus) across ca. 600 km 2 of coastal and estuarine waters in south-western Australia, to evaluate whether estuarine dolphins should be treated as a discrete management unit.2. Photo-identification data and tissue samples were collected in 2016 and 2017 in a study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 120 publications
0
11
0
Order By: Relevance
“…Resource partitioning of socially and spatially distinct groups has been noted in other cetacea [ 115 , 143 ]. Although stranding records and sightings data show that G. m. edwardii strand all around New Zealand, only two stranding hotspot locations [ 50 ] were explored here.…”
Section: Discussionmentioning
confidence: 99%
“…Resource partitioning of socially and spatially distinct groups has been noted in other cetacea [ 115 , 143 ]. Although stranding records and sightings data show that G. m. edwardii strand all around New Zealand, only two stranding hotspot locations [ 50 ] were explored here.…”
Section: Discussionmentioning
confidence: 99%
“…However, our findings showed that the distribution of humpback dolphins in the PRE was narrower, and their suitable habitat range could be smaller than previously expected in the PRE. The distribution of cetaceans is likely related to the internal structure of the population (Nicholson et al, 2021), and many studies have shown that the humpback dolphins population in the PRE has spatial heterogeneity in their survival rate, age compositions, nutrient status and pollutant accumulation (Gui et al, 2017;Chan, 2019;Zhang et al, 2019;Guo et al, 2020). The multiple dispersed core habitat areas of the dolphin populations recorded based on the identification of the dolphin distribution density in this study, indicates that number and distribution of the dolphin community structures (Chan, 2019) requires further exploration.…”
Section: Habitat Distribution and Environmental Characteristicsmentioning
confidence: 99%
“…Only individuals identified from excellent quality photographs (as per Nicholson et al, 2012) were added to the catalog. Supplemental information on births and deaths in the identified estuarine dolphin community (Nicholson et al, 2021b), as well as photographic confirmation of resident individuals being alive and present in the estuary, came from regular monitoring effort by the Mandurah Dolphin Volunteer Rescue Group and a tour operator, Mandurah Cruises. The resulting census-level data enabled demographic rates to be calculated directly for each age class and sex.…”
Section: Data Collection and Photo-identificationmentioning
confidence: 99%
“…Channel and comprised solely of individuals identified as part of social communities residing in coastal waters (Nicholson et al, 2021b). Thirteen transects were conducted in the estuary in 2018 ($109 hr) with additional effort conducted on six days ($40 hr).…”
Section: Effort and Group Encountersmentioning
confidence: 99%
See 1 more Smart Citation